1987
DOI: 10.1073/pnas.84.23.8448
|View full text |Cite
|
Sign up to set email alerts
|

Linoleic acid, but not cortisol, stimulates accumulation of casein by mouse mammary epithelial cells in serum-free collagen gel culture.

Abstract: A two-step culture system has been developed to analyze the role of hormones in casein accumulation by mammary epithelial cells obtained from adrenaiectomized and ovariectomized adult virgin mice. In the first step cells are grown inside collagen gel in medium containing insulin, epidermal growth factor (EGF), and linoleic acid for 9 days; these conditions stimulate very little casein accumulation. Following this growth phase the gels are released to float in medium containing insulin, prolactin, and linoleic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Similarly, the proliferation of normal mammary epithelial cells in primary culture is not absolutely dependent upon exogenous lipids; nevertheless, these cells are highly responsive to linoleate and specific phospholipids. In addition, the hormonal requirements for the differentiation of mouse mammary epithelial cells in vitro can be modulated by linoleate (24). These findings lead us to suggest that these epithelial cells, which grow and differentiate within an adipose tissue matrix, may utilize exogenous fatty acids supplied by the surrounding adipose cells during mammogenesis (4,24).…”
Section: Discussionmentioning
confidence: 95%
“…Similarly, the proliferation of normal mammary epithelial cells in primary culture is not absolutely dependent upon exogenous lipids; nevertheless, these cells are highly responsive to linoleate and specific phospholipids. In addition, the hormonal requirements for the differentiation of mouse mammary epithelial cells in vitro can be modulated by linoleate (24). These findings lead us to suggest that these epithelial cells, which grow and differentiate within an adipose tissue matrix, may utilize exogenous fatty acids supplied by the surrounding adipose cells during mammogenesis (4,24).…”
Section: Discussionmentioning
confidence: 95%
“…Siliconized lens paper has been widely used in whole mammary gland organ culture (Plaut et al, 1993) to permit the bidirectional diffusion of soluble factors between the culture medium and floated tissue. An alternative system (Levay-Young et al, 1987) incorporated a wire grid to support explants at the gas:medium interface. However, the potential for sedimentation of nonadherent cells from tissue explants onto the monolayer under study would likely confound cell growth assays.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several groups have reported that exogenous unsaturated fatty acids might influence lactogenesis. Whereas Nandi and colleagues found that β-casein synthesis by primary mammary epithelial cells was increased by linoleic acid in culture [ 103 ], a recent report identified the opposite effect in that both oleic and linoleic acids promoted the degradation of hormone-induced β-casein [ 104 ]. This latter finding may be explained by time-dependent changes in the response of mammary epithelial cells to these fatty acids in culture [ 105 ].…”
Section: Introductionmentioning
confidence: 99%